Current status of filariasis chemotherapy - Sugeng Juwono Mardihusodo, Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
Success of filariasis control still depends greatly on chemotherapy. piethylcarbamazine is so far considered as the most suitable and effective drug of filariasis in man. Its untoward reactions experienced by the treated individuals, long course of administration and incapability of removing all Wuchereria bancroftimicrofilariae in blood, however, initiate the search for more ideal antifilarials.A number of chemical compounds has been tested and shown to be active as filaricides in. experimental animals, and needs further intensive and careful clinical evaluation in man prior to its administration on a wider scale.Various methods of filaricide testing, using different filarial parasites and laboratory animals, and hindering factors arising in case of the production of a new antifflarial drug are discussed.Key Words: filariasis chemotherapy - diethylcarbamazine filaricides - filaricide testing - anÂ tifilarial drug